Zastosowanie benchmarkingu w systemach kontroli strategicznej w organizacji publicznej - Białas, Tomasz (Application of benchmarking in the design of a strategic control system for a public organization, 2006)
The paper presents issues encountered while applying benchmarking in the management of public organizations, with special focus on the support for the control function. It presents concepts of classifications of benchmarking into types and categories, and the potential behind its application in the public sector. Using benchmarking in public organizations becomes increasingly popular in recent years, and so more complex methods of its implementation are sought, including correlation with strategic control. The article describes chosen aspects of the support offered by benchmarking in the process of managing in a public organization, showing linkages to other processes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 515-522